What about race?: internalised dominance in the Opt Out Florida movement. Issue 2 (3rd July 2019) - Currin, Elizabeth; Schroeder, Stephanie; McCardle, Todd
ABSTRACT: Opt Out Florida, a largely White, middle-class social movement comprised of parents – most often, mothers – opposed to high-stakes standardised testing in U.S. public schools, has received media criticism for its homogeneity. This article elucidates that trend while simultaneously offering a more nuanced view, using theories of internalised dominance, colourblindness, and powerblindness to analyse Opt Out members' racial story lines and testimonies. These discursive frames underscore the paradox of a White, middle-class movement purportedly acting for social justice aims: to democratically solve the problem of high-stakes testing, Opt Out members must seek out diverse perspectives. Otherwise, they are not just opting out, but missing out.